2019
DOI: 10.2134/jeq2018.03.0120
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis on Nitrogen Retention by Buffer Zones

Abstract: Buffer zones, established between agricultural fields and water bodies, are widely used as a measure to reduce N in surface runoff and groundwater. However, the literature indicates inconsistent results on the N removal efficiency of buffer zones between studies. We performed a weighed meta-analysis on the buffer zone effects on NO 3 -N and total N in surface runoff and groundwater by summarizing 46 studies published between 1980 and 2017. The overall effects of buffer zones were a 33 (−48 to −17%, n = 25) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 29 publications
(55 reference statements)
0
42
0
5
Order By: Relevance
“…Many studies reported here documented multiple outcomes, exemplified by the ecosystem services assessment approaches combined in the assessment of IBZ designs (Zak et al, 2019). Studies here also reported varied effectiveness for nutrients—for example, where buffers are more effective at soluble N removal; dissolved P remains an issue (Valkama et al, 2019; Vidon et al, 2019). A range of widths was considered in the studies, but the suggestion is that narrow widths are less robust to key water quality functions (Dal Ferro et al, 2019; Jaynes and Isenhart, 2019).…”
Section: Future Research and Implementation Requirementsmentioning
confidence: 83%
See 4 more Smart Citations
“…Many studies reported here documented multiple outcomes, exemplified by the ecosystem services assessment approaches combined in the assessment of IBZ designs (Zak et al, 2019). Studies here also reported varied effectiveness for nutrients—for example, where buffers are more effective at soluble N removal; dissolved P remains an issue (Valkama et al, 2019; Vidon et al, 2019). A range of widths was considered in the studies, but the suggestion is that narrow widths are less robust to key water quality functions (Dal Ferro et al, 2019; Jaynes and Isenhart, 2019).…”
Section: Future Research and Implementation Requirementsmentioning
confidence: 83%
“…In their meta‐analysis across a great range in buffer widths, Valkama et al (2019) highlighted that buffer zones were more effective at reducing N in groundwater (70% reduction in NO 3 ) than in surface runoff (33% reduction). However, the meta‐analysis found that buffering effectiveness was reduced with buffer zone age and was unrelated to width.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 3 more Smart Citations